Ruthenium incorporation into hydrotalcites-derived mixed oxides for phenol hydrogenation: Role of Mg/Al molar ratio - Barroso-Martín, Isabel; Benmebirouk-Pareja, Nadia; Montaña, Maia; Cecilia-Buenestado, Juan Antonio; Infantes-Molina, Antonia; Rodríguez-Castellón, Enrique (Elsevier, 2023)
In this work the catalytic behaviour of Ru supported on mixed oxides derived from non-commercial hydrotalcites in phenol hydrogenation was studied in a batch reactor working at 30 bar and 200 °C. To this end, a set of catalysts with 2 wt% Ru and a Mg/Al molar ratio of 1, 2, 3 and 4 was synthesized. The catalysts were tested in phenol hydrogenation to assess the influence of Mg/Al ratio on the catalytic performance in terms of conversion and selectivities to cyclohexanol and cyclohexanone. Physicochemical characterization was performed by X-ray Diffraction (XRD), N2 adsorption-desorption isotherms, dispersive X-ray spectroscopy in scanning transmission electron microscopy (EDS-STEM), CO chemisorption at 35 °C, CO2 and NH3 thermoprogrammed desorption (TPD) and X-ray Photoelectron Spectroscopy (XPS). The Mg/Al molar ratio employed determined the catalytic response of the resulting catalysts, obtaining the best catalytic performance (95.9 % conversion and 47.4 % cyclohexanone selectivity) with the sample with the lowest Mg/Al ratio, RuMA1. XRD results showed that in RuMA1 catalyst the hydrotalcite structure was completely transformed into the corresponding mixed oxide after thermal treatment and was also the only one in which MgAl2O4 spinel was not formed. In addition, RuMA1 presented the highest specific surface area, the greatest Ru dispersion, as evidenced by CO-chemisorption and EDX-STEM analysis, as well as a good balance between basic and acid sites and a greater proportion of Bronsted acid sites that also explain it greater selectivity to cyclohexanol.
Keywords: Óxidos; Catalizadores; Rutenio; Hidrogenación; Fenol; Elementos químicos; Hydrotalcites; Mixed oxides; Ruthenium catalysts; Hydrogenation; Phenol; Catálisis